Assessing Dietary Phosphorus Intake and Serum Phosphorus in Adults with Liver Conditions: NHANES 2015–2016. (29th May 2020) - Muthuraju, Sowmiya; Miketinas, Derek
Abstract: Objectives: Patients with liver conditions may have increased phosphorus turnover which can increase the risk of severe hypophosphatemia and other complications. The objective of this cross-sectional study was to quantify the usual intake of phosphorus, assess serum phosphorus (SP) levels across levels of liver conditions, and to estimate and assess the odds for having critically low phosphorus levels across adults with and without liver conditions. Methods: Data were obtained from the NHANES 2015–2016 cycle. Adults were divided into four groups based on self-reported responses from the NHANES medical history questionnaire: liver cancer (LC), unspecified current liver condition (CLC), unspecified resolved liver condition (RLC), and no liver condition. Usual intake was estimated using the NCI method and all analyses were adjusted to account for the complex, multistage, probability sampling design. Results: Usual phosphorus intake was highest in participants with RLC (1399 ± 26.5 mg) and lowest in participants with LC (1267 ± 140.7 mg). Although the percentage of those meeting the EAR for phosphorus was high (>95%), SP levels are lowest in participants with LC. SP levels differed slightly across liver conditions: participants with LC had a SP level of 1.0 ± 0.07 mmol/L, while participants with CLC, RLC, or no liver conditions had SP levels of 1.2 ± 0.01 mmol/L, 1.2 ± 0.01 mmol/L, and 1.2 ± 0.02 mmol/L, respectively. Participants with CLC had a usual phosphorus intake of 1350 ± 49.6 mg, and those who had no liver conditions had a usual phosphorus intake of 1387 ± 18.5 mg. The odds for normal phosphorus levels in participants with LC was low (Odds = 0.06; 95% CI: 0.01–0.45); the odds for CLC participants having normal SP levels was 1.6 (95% CI: 1.2–2.15); the odds for normal SP levels in participants with RLC were 2.2 (95% CI: 1.3–3.75), and the odds for normal SP in participants with no liver conditions odds for low were 1.9, (95% CI: 1.71–2.14). Conclusions: These results indicate that patients with liver cancer are at higher risk of hypophosphatemia, and that phosphorus recommendations for patients with liver cancer may need to be adjusted. However, the variability in this subpopulation with liver cancer is high and warrants further investigation. Funding Sources: None.